KAJIAN MORFOMETRI DANAU PONDOK LAPAN DESA NAMAN JAHE KECAMATAN SALAPIAN KABUPATEN LANGKAT (MORPHOMETRY STUDY OF PONDOK LAPAN LAKE DESA NAMAN JAHE KECAMATAN SALAPIAN KABUPATEN LANGKAT) - Muhammad Ma’rufi; Yunasfi Djayus; Ahmad Muhtadi (AQUACOASTMARINE, 2015)
Morphometry and water quality are primary data to assessing the potential of the lake.Morphometry data of lake is need in determining the lake’s layers and also determine theability to use by people. Pondok Lapan Lake is an artificial lake which located in Langkat.The purpose of this study was to determine the morphometric of aspects Pondok Lapan Lakeand determine the capacity that might be. The research was conducted from January untilMarch 2015. Data collection were performed in this research that were depth, stream flow,and around the lake are processed using ArcView. From the results, the lake morphometricaspects of wide Pondok Lapan Lake is around 63.472,78 m², the maximum length of 548,28m, 220,23 m maximum width, circumference 2.200,83 m, maximum depth of 4.15 m, with asloping bottom waters and shape of the lake bottom surface is irregular. And the capacity ofthe Pondok Lapan Lake which can be used by the public is 153.484,43 m³ of water volume,stream flow around 12.963,456 m³/day-14.111,712 m³/day, Recidance time of water about11-12 days, the brightness of the water approximately 0,965 m – 1,056 m with a depth ofcompensation approximately 2,612 - 2,858 mKeywords : Pondok Lapan Lake, lake morphometry, lake capacity